Kelakai serum reduces UVB-induced vascular endothelial growth factor and interleukin-6: in vivo study - Ulfadhina, Nedya; Hussaana, Atina; Suparmi, Suparmi (Universitas Muhammadiyah Purwokerto, 2025)
Background: UVB exposure increases reactive oxygen species leading to higher expression of vascular endothelial growth factor (VEGF) and interleukin-6 (IL-6), which accelerate photoaging. Kelakai leaf (Stenochlaena palustris) contains flavonoids and phenolic compounds with antioxidant and anti-inflammatory potential, yet its efficacy in serum formulations has not been evaluated. Purpose: To determine the effect of kelakai leaf extract serum on VEGF and IL-6 expression in BALB/c mice exposed to subchronic UVB radiation. Method: This experimental post-test only control group study used 30 BALB/c mice assigned to five groups: healthy control (K1), UVB-exposed negative control (K2), UVB + 0.025% retinoid serum (K3), UVB + 2% kelakai serum (K4), and UVB + 4% kelakai serum (K5). UVB exposure (160 mJ/cm²) was given for 14 days followed by topical treatment. Skin tissues were examined using immunohistochemistry to assess VEGF and IL-6 expression. Data were analyzed using the Kruskal–Wallis test followed by Mann–Whitney. Results: VEGF and IL-6 expression were highest in K2 and lowest in K1. Both retinoid and kelakai serum significantly reduced expression levels (p<0.05). The 4% kelakai serum (K5) produced greater reductions than the 2% dose, approaching the effect of retinoid serum. Conclusion: Kelakai leaf extract serum at 4% effectively decreases VEGF and IL-6 expression in UVB-exposed mice, supporting its potential as a natural anti-photoaging agent.